(untitled) (Journal of Educational Sciences, 2024)
The article examines the application of ethnopedagogical and ethnopsychological foundations in the preparation of primary school teachers. The authors postulate ethnopedagogical values and principles in the upbringing of the new generation of children as well as future educators. The utilization of national peculiarities in the process of professional training of future elementary school teachers is linked to teaching national-cultural values to children. Future teachers of elementary classes are professionals who will first impart national-cultural knowledge to first graders. Therefore, the aim of the research was to summarize the methods of developing ethnopsychological and ethnopedagogical traditions of the Kazakh people in the professional training of future elementary school teachers. The research results can be applied in pedagogical education. The novelty of the study lies in proposing 10 conditions for improving the preparation of future elementary school teachers based on ethnopsychological and ethnopedagogical foundations, as well as traditions of the Kazakh people. A program for an elective course "Ethnopedagogy and Ethnopsychology for Personality Development" is suggested. The empirical part of the study included surveying students and conducting interviews with 23 students from Kyzylorda Korkyt Ata University about the possibilities of applying ethnopedagogical knowledge in the professional activities of elementary school teachers in national schools. Keywords: primary school teachers, professional training, primary education, ethnopsychological characteristics, ethnopedagogical characteristics, personality, national pedagogy.